The anatomy of halal slaughtering: Issues and challenges / Sharifah Zannierah Syed Marzuki … [et al.] - Syed Marzuki, Sharifah Zannierah; Mat Yunus, Nor Khairunnisa; Abu Yazid, Zaidatul Nadiah; Ismail, Ida Rosnita (2012)
A relevant issue pertaining to the values of Muslims dietary restriction is the concept of farm to fork that is guided by the Islamic Dietary Law. Therefore, it is important for the Muslims to know the source of food that they eat. In essence, Islamic religion inspired requirements that focused on spirituality is developed through many compositions and one of them is food. Most of the dietary restrictions placed on Muslims fall in the domain of animal kingdom, especially land animals. Thus, halal slaughtering method must be applied to halal animals. This paper aims to discuss the structure of halal slaughtering as public debate on slaughtering and stunning of animals are indefinitely discussed with the issues of animal cruelty and animal welfare.